Work, unions and co-determination 1981 - Hörte, Sven-Åke; Hart, Horst (University of Gothenburg, 1984)
In 1977 a new law called 'Act on Co-determination' came into force in Sweden. According to this law trade unions have the right to be informed about all circumstances that are, or could be, of importance for the members of the union. The unions have the right to express their opinions on almost every important question at 'the establishment'. This is allowed for in a special type of negotiation. An employer has after negotiations however the right to make a decision without bothering about the union's opinion. This law is supposed to regulate the unions rights to participate in the decision making process at the establishment. It is an important part of the complex system of formal norms that regulates the relations between trade unions and employers in Sweden. The research project 'Work, Unions and participation' studied how local actors - unions and employers - have adapted to this system of norms.
This study is composed of two survey studies, designed as a panel study. The population is restricted to following branches: manufacturing, trade, transports and communications, education, social welfare and public health. The sample size is about 500 establishments, which means 25% of the population. Two types of questionnaires were sent to respondents at these places of work. One was sent to the local leadership, which was usually answered by the local manager or an equivalent person, one questionnaire was sent to each of the trade unions which were active at the place of work.

In 1977 a new law called 'Act on Co-determination' came into force in Sweden. According to this law trade unions have the right to be informed about all circumstances that are, or could be, of importance for the members of the union. The unions have the right to express their opinions on almost every important question at 'the establishment'. This is allowed for in a special type of negotiation. An employer has after negotiations however the right to make a decision without bothering about the union's opinion. This law is supposed to regulate the unions rights to participate in the decision making process at the establishment. It is an important part of the complex system of formal norms that regulates the relations between trade unions and employers in Sweden. The research project 'Work, Unions and participation' studied how local actors - unions and employers - have adapted to this system of norms.
This study is composed of two survey studies, designed as a panel study. The population is restricted to following branches: manufacturing, trade, transports and communications, education, social welfare and public health. The sample size is about 500 establishments, which means 25% of the population. Two types of questionnaires were sent to respondents at these places of work. One was sent to the local leadership, which was usually answered by the local manager or an equivalent person, one questionnaire was sent to each of the trade unions which were active at the place of work.
Arbetet, facket och medbestämmandet 1981
Keywords: trade unions; fackföreningar; working conditions; arbetsförhållanden; Labour relations/conflict; Förhållande/konflikter mellan arbetsmarknadens parter; Working conditions; Arbetsförhållanden; Social Sciences; Samhällsvetenskap; Sociology; Sociologi